Gastroprotection and mucus stimulation by vitamin D3 in pyloric ligation and Indomethacin-induced gastric ulcers rats models - Harrison Oghogho Otamere; Uwaifoh Akpamu (Archives of Clinical Gastroenterology - Peertechz Publications, 2021)
The effect of vitamin D3 (VD3) on gastric ulcers was investigated by evaluating ulcer index, biochemical aggressive, and protective factors. Rats were divided into 4 groups; untreated indomethacin ulcer, VD3 pre-treated + indomethacin ulcer, untreated pyloric-ligation ulcer and VD3 pre-treated + pyloric-ligation ulcer. Treatment with VD3 (400 IU/kg intramuscular) was done daily for 6 days and an hour before ulcers induction. Four hours post-induction, the blood sample was obtained for the determinations of 1,25-dihydroxy vitamin D (1,25-DHCC), Parathyroid Hormone (PTH), and Calcium (Ca). Laparotomy was performed and the stomach was harvested for gastric acidity, ulcer index, and biochemical evaluations. The data were analyzed using statistical tools and the "student t-test" was performed at p<0.05. VD3 pre-treatmment caused an increase in serum levels of 1,25-DHCC, has no significant effect on PTH and Ca levels but decreased gastric acidity and ulcer index (p<0.05) with protective ratios of 42.11% and 60.00% against indomethacin and pyloric-ligation ulcers respectively. Pretreatment resulted in decreased gastric MDA, increased gastric protein, mucin, and nitric oxide levels. Gastric protection by VD3 was through oxidative stress inhibition and stimulation of mucus and blood flow against indomethacin and pyloric ligation gastric damage.